Optic Nerve Atrophy in Heroin Intoxication - E. E. Ioyleva; A. V. Zinov’eva (Oftalʹmologiâ, 2020)
Drug dependence is one of important social problems in modern society. It became more actual because of the high morbidity in young working-age patients. The central nervous system is the main target for psychoactive substances. Long-term drug intoxication results in functional and structural brain alterations, it leads to cognitive impairment and disturbances of higher mental functions rendering patients’ disadapted in their work and daily life activities. Eye disorders due to drug abuse are multifaceted and can vary from conjunctival damage to severe endogenous endophthalmitis. Opioid dependence can result not only from intentional self-administration of narcotic drugs, but also from long-term prescribed use of these medicinal products owing to their potent analgesic effect exhibited in somatically ill patients with severe chronic pain. Opioid derivatives act as partial or full agonists of three types of opioid receptors (δ, κ, and µ) extensively expressed by the neurons of the central and, to a lesser extent, peripheral nervous system. The most dangerous complication of intoxication with this group narcotic drugs is opioid induced-respiratory depression resulting in hypoxaemia and hypercapnia. The paper presents a case report of bilateral optic nerve atrophy that developed in a young female patient after a long period of intravenous heroin use. There are practically no reports of optic nerve damage due to heroin intoxication in the current literature. Possible optic nerve atrophy mechanisms under discussion include generalized hypoxia developing against a background of chronic heroin intoxication and direct toxicity of admixtures used to dilute home-made narcotic drugs. In view of the growing use of these substances, physicians have to consider their effects in the differential diagnosis in patients with atypical eye disorders.